Performance of inertial measurement units to classify different upper limb activities in elite women`s water polo: a cross sectional study - King, M.; Lewis, A.; Watson, K.; Vicenzino, B. (British Journal of Sports Medicine, 2021)
Background Water polo had the highest injury incidence of all team sports at the 2016 Rio Olympics. Injuries have been linked to external load in training and competition (Mountjoy et al, 2015, Wheeler et al, 2013). External load monitoring is likely instructive in managing loads to optimise performance while minimising injury risk. Inertial measurement units and machine learning techniques have shown promise in other sports in monitory external load.